You ask. (Journal of Parents and Teachers, 2025)
The article describes how teachers should interact with students; that is, they must pay attention to small details, show curiosity, be attentive, encourage research, and consider a long list of factors. Additionally, parents continuously demand measurable operational projects, yet they do not value the achievements.
Keywords: parents; teachers; students; details